Program MBG di Indonesia: Tinjauan kasus korupsi dan kelemahan pengawasan - Hidayah, Ulfi (Maliki Interdisciplinary Journal, 2026)
Corruption is a serious problem that remains a major challenge in governance in Indonesia because it not only harms state finances but also hinders public welfare and undermines public trust in government institutions. This study aims to analyze the phenomenon of corruption in the MBG Program in Indonesia by highlighting the forms of deviation and weaknesses in the oversight system that occur. The method used is a qualitative approach with literature review techniques through a review of various relevant scientific sources. The results of the discussion indicate that corruption in the MBG Program can occur in various forms, such as budget misuse, data manipulation, and nepotism. Causal factors include low individual integrity, a weak oversight system, a lack of transparency, and a lack of firmness in law enforcement. Furthermore, inequality is still found in the handling of corruption cases, indicating a suboptimal legal system. The impact of these practices is very significant, particularly in reducing program effectiveness, hindering the distribution of targeted aid, and weakening public trust. Therefore, comprehensive improvement efforts are needed through strengthening the oversight system, increasing transparency and accountability, and firm and fair law enforcement. In addition, instilling moral values ​​such as honesty and responsibility through anti-corruption education is also an important step in preventing corrupt practices so that the program can run optimally and provide maximum benefits to the community.